Clinical study of total bone marrow combined with total lymphatic irradiation pretreatment based on tomotherapy in hematopoietic stem cell transplantation of acute leukemia - Kong, Fanyang; Liu, Shuaipeng; Liu, Lele; Pi, Yifei; Pei, Yuntong; Xu, Dandan; Jia, Fei; Han, Bin; Guo, Yuexin (Frontiers in Oncology, 2022)
Objective Allogeneic hematopoietic stem cell transplantation（allo-HSCT） is an effective method for the treatment of refractory and relapsed acute leukemia, and the preconditioning methods before transplantationis one of the important factors affecting the survival of patients. Radiotherapy combined with chemotherapy is the most commonly used preconditioning method before transplantation. This study evaluated the safety and efficacy of total bone marrow combined with total lymphatic irradiation as a preconditioning method before hematopoietic stem cell transplantation. Methods Twelve patients with acute leukemia who were admitted to our center from 2016 to 2020 were selected. The median age was 17 years (8-35). The target area for TMLI includes the total bone marrow and total lymphatic space, and the organs at risk include the lens, lungs, kidneys, intestine, heart, and liver. The patients received a total bone marrow and lymphatic irradiation preconditioning regimen, the related acute adverse reactions were graded, and the prognosis of the patients after transplantation was observed. Results During patient preconditioning, only grade 1-2 toxicity was observed, and grade 3-4 toxicity did not occur. Except for one patient whose platelets were not engrafted, all the other patients were successfully transplanted. The median time of neutrophil implantation was 14 d (9-15 d), and the median time of platelet implantation was 14 d (13-21 d). With a median follow-up of 9 months (2-48), 4 relapses occurred, 3 died, and 10 leukemia patients survived and were disease-free. One-year overall survival was 69.8%, cumulative recurrence was 19.5% , disease-free-survival was 54.2%.Conclusion The Allo-HSCT pretreatment regimen of total bone marrow combined with total lymphatic irradiation is safe and effective in the treatment of malignant hematological diseases. Total bone marrow combined with total lymphatic irradiation may completely replace total body irradiation, and the clinically observed incidence of acute toxicity is not high.